Comparison of Thermo-physical Properties of Mg-Ga and Mg-Pb Alloys at 1000 K - Panthi, N.; Bhandari, I. B.; Pangeni, R. C.; Koirala, I. (Journal of Institute of Science and Technology, 2021)
Concentration-dependent thermophysical properties of molten Mg-Pb and Mg-Ga alloys at 1000 K was compared using the Redlich Kister equation by optimizing exponential interaction energy parameters based on the R-K polynomials framework. The mixing behavior was investigated by giving more emphasis to the role of temperature-dependent interaction energy parameters. Our study shows that the magnesium gallium alloy is slightly interacting than the magnesium lead alloy. The surface tension and viscosity of both alloys was compared using the Butler equation as improved by Kaptay and KRP (Kozlov-Ronanov-Petrov) approach respectively. The surface tension of Mg-Pb liquid alloy increases but decreases in Mg-Ga alloy with an increase in the concentration of Mg. The viscosity has a nonlinear variation for both alloys with the increase in the concentration of magnesium.